Hot isostatic pressing elimination of process-induced defects in laser powder bed fusion fabricated DZ125 superalloy: Microstructure evolution and mechanical property enhancement - Hairui Gao; Zhenwu Zhang; Jikang Li; Jiangtao Sun; Honghao Xiang; Boyang Wu; Wei Li; Chao Cai; Qingsong Wei (Journal of Materials Research and Technology)
This study systematically investigated the crack formation mechanisms in DZ125 nickel-based superalloy fabricated by laser powder bed fusion (LPBF) and evaluated the effectiveness of hot isostatic pressing (HIP) in defect elimination, microstructural modification, and mechanical property enhancement. The results revealed that the cracks in LPBF-processed DZ125 alloy are primarily solidification cracks and liquation cracks, whose formation is associated with thermal stress concentration and low-melting-point eutectic phases induced by segregation of Hf/Ti elements. The conduction-mode melt pools (with an aspect ratio ≈0.5) formed at high scanning speeds effectively mitigated crack formation. After HIP treatments at different temperatures (1050 °C, 1150 °C, and 1230 °C), both cracks and pores were significantly reduced, with near-complete densification and almost full recrystallization achieved at 1230 °C. Increasing HIP temperature leads to γ′ phase coarsening and columnar-to-equiaxed grain transformation. The 1050°C–HIP samples exhibited enhanced yield strength (859 MPa) due to precipitation of fine γ′ phases (∼100 nm), while the 1150 °C and 1230°C–HIP samples show reduced yield strength but significantly improved elongation (17.5 % and 21.8 %, respectively) owing to γ′ coarsening and recrystallization. This work provides crucial insights for defect control and performance optimization of LPBF-fabricated DZ125 superalloy.